PENGARUH PENDEKATAN KONTEKSTUAL BERBANTUAN MEDIA REALIA TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA KELAS IV SD NEGERI PEMATANG PURBA - Yunita Lingga; Nur Hudayah M., M.Pd; Dr.Elvi Mailani, S.Si; M.Pd, Fahrur Rozi, S.Pd., M.Pd; Lidia Simanihuruk, S.Si., M.Pd (STKIP Subang, 2026)
YUNITA LINGGA. The Effect of a Contextual Approach Assisted by Realia Media on the Mathematical Problem-Solving Ability of Fourth-Grade Students of Pematang Purba State Elementary School. Thesis. Medan: Faculty of Education, Medan State University 2026. This study aims to determine the effect of a contextual approach assisted by realia media on the mathematical problem-solving ability of fourth-grade students of Pematang Purba State Elementary School. The study sample consisted of 42 students, divided into two groups: an experimental group using realia media and a control group that did not use the media. This study used a quantitative approach with a Quasi-experimental design method and a Pretest-Posttest Nonequivalent Control Group Design. Research data were collected through interviews, tests, and documentation. The data obtained were analyzed using normality tests, homogeneity tests, and hypothesis tests. The results showed a significant effect of the contextual approach assisted by realia media on mathematical problem-solving ability. This is indicated by the average pretest score in the control class of 59.52 and the average posttest score in the control class of 70.95, while the average pretest score in the experimental class was 71.34 and the average posttest score in the experimental class was 85.54. The results of the independent sample t-test showed a sig value (2-tailed) = 0.001 < 0.05, meaning the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. Thus, the use of a contextual approach using realia media has been proven to have a significant influence on students' problem-solving abilities.